Business ethics of Singtel & PLDT a comparative analysis of the language codes of conduct of two ASEAN telco companies using MAK Halliday's systemic functional grammar - Benauro, Rowena N.; Hernandez, Tara Jasmin U. (College of Arts and Letters, University of the Philippines Diliman, 2018)
The ASEAN integration brings about greater labor mobility within the region. Because of this phenomenon, work environments within the ASEAN are expected to become more diverse, not only in terms of culture but also in terms of business practices an business ethics. A Filipino accountant, for instance, may have to subscribe to a different set of accounting ethics when he works in Singapore. Scholars such as Jakubowski (2002) believe that understanding the similarities and differences in the business ethics between countries should prove useful to those who wish to work in foreign countries. The present work is thus an attempt to understand the similarities and differences between the business ethics of Singapore Telecommunications LTD (Singtel) and Philippine Long Distance Telephone Company, Inc. (PLDT) by looking at the linguistic choices made in these companies' codes of conduct. The researchers then ask "What do the linguistic choices made in the codes of conduct of Singtel and PLDT reveal about the business ethics". In order to answer this problem, the researchers conduct a qualitative comparative analysis of the lexicogrammar of the clauses in the code using MAK Halliday's systemic functional grammar. Particularly, the researchers study the transitivity, modd (and modulation), theme-rheme systems and explore the meanings made through the systemic choices in terms of ideational, interpersonal, and textual metafunctions. The study revealed that the Singtel code and the PLDT code reflected very different choices in terms of the transitivity, mood (and modulation), theme-rheme systems. The Singtel code relies heavily on relational clauses, make use of indicative mood with high incidence of modulation and gives thematic importance to employees. The PLDT code is mostly material in process, imperative in mood, and is focused largely on action words. These linguistic choices highlight the differences in which these companies from different countries convey their business ethics and impose on or expect ethical responsibilities from their stakeholders.